Incremental Complex Products

Algebra Level 5

Let a , b , c a,b,c be complex numbers satisfying

( a + 1 ) ( b + 1 ) ( c + 1 ) = 1 (a+1)(b+1)(c+1) = 1

( a + 2 ) ( b + 2 ) ( c + 2 ) = 2 (a+2)(b+2)(c+2) = 2

( a + 3 ) ( b + 3 ) ( c + 3 ) = 3 (a+3)(b+3)(c+3) = 3

Find ( a + 4 ) ( b + 4 ) ( c + 4 ) (a+4)(b+4)(c+4) .


The answer is 10.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Discussions for this problem are now closed

Let P ( x ) P(x) be a monic polynomial with roots a a , b b and c c : P ( x ) = ( x a ) ( x b ) ( x c ) P(x)=(x-a)(x-b)(x-c)

We know that:

P ( 1 ) = ( a + 1 ) ( b + 1 ) ( c + 1 ) = 1 P ( 2 ) = ( a + 2 ) ( b + 2 ) ( c + 2 ) = 2 P ( 3 ) = ( a + 3 ) ( b + 3 ) ( c + 3 ) = 3 -P(-1)=(a+1)(b+1)(c+1)=1\\ -P(-2)=(a+2)(b+2)(c+2)=2\\ -P(-3)=(a+3)(b+3)(c+3)=3

By inspection, we say that P ( x ) = ( x + 1 ) ( x + 2 ) ( x + 3 ) + x P(x)=(x+1)(x+2)(x+3)+x .

So,

P ( 4 ) = ( a + 4 ) ( b + 4 ) ( c + 4 ) = ( ( 4 + 1 ) ( 4 + 2 ) ( 4 + 3 ) + ( 4 ) ) = 10 \begin{aligned} -P(-4) & =& (a+4)(b+4)(c+4) \\ & =& -((-4+1)(-4+2)(-4+3)+(-4)) \\ & =& \boxed{10} \\ \end{aligned}

superbbb...approach

Arnav Das - 6 years, 3 months ago

Great approach. This was my first thought too :)

Calvin Lin Staff - 6 years, 4 months ago

Did the same way!

Ajith Kumar - 6 years, 4 months ago

Let f ( x ) = ( x + a ) ( x + b ) ( x + c ) = x 3 + ( a + b + c ) x 2 + ( a b + b c + c a ) x + a b c f(x) = (x+a)(x+b)(x+c) = x^3 +(a+b+c)x^2+(ab+bc+ca)x +abc = x 3 + p x 2 + q x + r = x^3 +px^2+qx+r where p = a + b + c , q = a b + b c + c a p = a+b+c, q=ab+bc+ca and r = a b c r = abc . \\ Now f ( 1 ) = 1 p + q + r = 0 ( 1 ) f ( 2 ) = 2 4 p + 2 q + r = 6 ( 2 ) f ( 3 ) = 3 9 p + 3 q + 4 = 24 ( 3 ) S o l v i n g ( 1 ) , ( 2 ) a n d ( 3 ) , p = 6 , q = 12 , r = 6. H e n c e f ( x ) = x 3 6 x 2 + 12 x 6. T h u s f ( 4 ) = 10 f(1) = 1 \Rightarrow p+q+r = 0 ---------(1) \\ f(2) = 2 \Rightarrow 4p+2q+r = -6 -------(2) \\ f(3) = 3 \Rightarrow 9p+3q+4 = -24 -------(3) \\ Solving (1),(2) and (3), p = -6, q = 12 , r = -6. \\ Hence f(x) = x^3 -6x^2+12x-6. \\ Thus f(4) = 10

I solved it this way :)

Maribel Omega - 6 years, 3 months ago

compact and correct!

Arkadeep Sarkar - 6 years, 4 months ago

Firstly, let's expand all of the equations.

a b c + a b + a c + b c + a + b + c + 1 = 1 ( I ) abc + ab + ac + bc + a + b + c + 1 = 1 \,(I)

a b c + 2 a b + 2 a c + 2 b c + 4 a + 4 b + 4 c + 8 = 2 ( I I ) abc + 2ab + 2ac + 2bc + 4a + 4b + 4c + 8 = 2\,(II)

a b c + 3 a b + 3 a c + 3 b c + 9 a + 9 b + 9 c + 27 = 3 ( I I I ) abc + 3ab + 3ac + 3bc + 9a + 9b + 9c + 27 = 3\,(III)

Subtracting ( I ) (I) from ( I I ) (II) and ( I I ) (II) from ( I I I ) (III) , we get:

a b + a c + b c + 3 a + 3 b + 3 c + 7 = 1 ( I V ) ab + ac + bc + 3a + 3b + 3c + 7 = 1\,(IV)

a b + a c + b c + 5 a + 5 b + 5 c + 19 = 1 ( V ) ab + ac + bc + 5a + 5b + 5c + 19 = 1\,(V)

Subtracting ( I V ) (IV) from ( V ) (V) :

2 a + 2 b + 2 c + 12 = 0 2a + 2b + 2c + 12 = 0

a + b + c = 6 ( V I ) a + b + c = -6\,(VI)

Substituting ( V I ) (VI) in ( I V ) (IV) , we get:

a b + a c + b c + 3 6 + 7 = 1 ab + ac + bc + 3*-6 + 7 = 1

a b + a c + b c 18 + 7 = 1 ab + ac + bc - 18 + 7 = 1

a b + a c + b c = 12 ( V I I ) ab + ac + bc = 12\,(VII)

Substituting ( V I ) (VI) and ( V I I ) (VII) in ( I ) (I) :

a b c + 12 6 + 1 = 1 abc + 12 - 6 + 1 = 1

a b c = 6 ( V I I I ) abc = -6\,(VIII)

Now we have all of the information we need:

( a + 4 ) ( b + 4 ) ( c + 4 ) = a b c + 4 ( a b + a c + b c ) + 16 ( a + b + c ) + 64 (a + 4)(b + 4)(c + 4) = abc + 4(ab + ac + bc) + 16(a + b + c) + 64

= 6 + 4 12 + 16 6 + 64 = 6 + 48 96 + 64 = 112 102 = 10 = -6 + 4*12 + 16*-6 + 64 = -6 + 48 - 96 + 64 = 112 - 102 = 10 .

I did it this way except I noticed that there were the 1st, 2nd, and 3rd symmetric sums so I rewrote them each as e1, e2, and e3.

Hobart Pao - 6 years, 4 months ago

i did the same way and find answer.

snigdh chaturvedi - 6 years, 4 months ago

I did the same way..!!

Anuj Agarwal - 6 years, 4 months ago

This is how I was solving it but got 4 3 4^3 wrong. I had it 256 instead of 64.

Roman Frago - 6 years, 4 months ago
Jason Hughes
Jan 27, 2015

Let a + 1 = x , b + 1 = y a+1=x, b+1=y , and c + 1 = z c+1=z . So x y z = 1 xyz=1 , ( x + 1 ) ( y + 1 ) ( z + 1 ) = 2 (x+1)(y+1)(z+1)=2 , ( x + 2 ) ( y + 2 ) ( z + 2 ) = 3 (x+2)(y+2)(z+2)=3 , and now I want to find ( x + 3 ) ( y + 3 ) ( z + 3 ) (x+3)(y+3)(z+3) .

Expand ( x + 1 ) ( y + 1 ) ( z + 1 ) = 2 (x+1)(y+1)(z+1)=2 and ( x + 2 ) ( y + 2 ) ( z + 2 ) = 3 (x+2)(y+2)(z+2)=3 to x y z + x y + x z + y z + x + y + z + 1 = 2 xyz+xy+xz+yz+x+y+z+1=2 , and x y z + 2 x y + 2 x z + 2 y z + 4 x + 4 y + 4 x + 8 = 3 xyz+2xy+2xz+2yz+4x+4y+4x+8=3 .

Then substitute x y z xyz for 1 1 and simplify to get x y + y z + x z + x + y + z = 0 xy+yz+xz+x+y+z=0 , and x y + x z + y z + 2 x + 2 y + 2 z = 3 xy+xz+yz+2x+2y+2z=-3 .

Subtract the first from the second two to get: x + y + z = 3 x+y+z=-3 .

Then get x y + x z + y z = 3 xy+xz+yz=3 by sustituting x + y + z = 3 x+y+z=-3 into the first equation. Expand what we want to find to get: ( x + 3 ) ( y + 3 ) ( z + 3 ) = x y z + 3 ( x y + x z + y z ) + 9 ( x + y + z ) + 27 (x+3)(y+3)(z+3) = xyz+3(xy+xz+yz)+9(x+y+z)+27 . Substitute out x y z , x y + y z + x z xyz, xy+yz+xz , and x + y + z . 1 + 3 ( 3 ) + 9 ( 3 ) + 27 = 10 x+y+z. 1+3(3)+9(-3)+27=10 .

William Chau
Feb 2, 2015

Let x = a + 2 x = a+2 , y = b + 2 y = b+2 , and z = c + 2 z = c+2 . So the system is equivalent to ( x 1 ) ( y 1 ) ( z 1 ) = 1 ; x y z = 2 ; ( x + 1 ) ( y + 1 ) ( z + 1 ) = 3 , (x-1)(y-1)(z-1) = 1; xyz = 2; (x+1)(y+1)(z+1) = 3, 2 ( x y + y z + z x ) + x + y + z 1 = 1 , x y z = 2 ; 2 + ( x y + y z + z x ) + ( x + y + z ) + 1 = 3 , 2-(xy+yz+zx)+x+y+z-1 = 1, xyz = 2; 2+(xy+yz+zx)+(x+y+z)+1 = 3, ( x + y + z ) ( x y + y z + z x ) = 0 , x y z = 2 ; ( x + y + z ) + ( x y + y z + z x ) = 0 , (x+y+z)-(xy+yz+zx) = 0, xyz = 2; (x+y+z)+(xy+yz+zx) = 0, x + y + z = x y + y z + z x = 0 ; x y z = 2. x+y+z = xy+yz+zx = 0; xyz = 2. Now, ( a + 4 ) ( b + 4 ) ( c + 4 ) = ( x + 2 ) ( y + 2 ) ( z + 2 ) = x y z + 2 ( x y + y z + z x ) + 4 ( x + y + z ) + 8 = 2 + 2 0 + 4 0 + 8 = 10. (a+4)(b+4)(c+4) = (x+2)(y+2)(z+2) = xyz+2(xy+yz+zx)+4(x+y+z)+8 = 2+2\cdot 0+4\cdot 0+8 = 10.

Use x = a + 2 , y = b + 2 , z = c + 2 x=a+2,y=b+2,z=c+2 so the equation becomes

( x 1 ) ( y 1 ) ( z 1 ) = 1 (x-1)(y-1)(z-1)=1 ( e q . 1 ) (eq.1)

x y z = 2 xyz=2 ( e q . 2 ) (eq.2)

( x + 1 ) ( y + 1 ) ( z + 1 ) = 3 (x+1)(y+1)(z+1)=3 ( e q . 3 ) (eq.3)

Expanding the first and the third equations gives:

( e q . 1 ) (eq.1) : x y z x z x y y z + x + y + z 1 = 1 xyz-xz-xy-yz+x+y+z-1=1

( e q . 3 ) (eq.3) : x y z + x z + x y + y z + x + y + z + 1 = 3 xyz+xz+xy+yz+x+y+z+1=3

Substitution and rearranging:

( e q . 1 ) (eq.1) : 2 ( x z + x y + y z ) + x + y + z = 2 2-(xz+xy+yz)+x+y+z=2

( e q . 2 ) (eq.2) : 2 + ( x z + x y + y x ) + x + y + z = 2 2+(xz+xy+yx)+x+y+z=2

Subtracting ( ( e q . 3 ) ( e q . 1 ) (eq.3)-(eq.1) yields: 2 ( x z + x y + y z ) = 0 2(xz+xy+yz)=0 , so x z + x y + y z = 0 \boxed{xz+xy+yz=0}

Substitute this value back to either the first or the third equation:

( e q . 1 ) (eq.1) : 2 ( x z + x y + y z ) + x + y + z = 2 2 ( 0 ) + x + y + z = 2 2-(xz+xy+yz)+x+y+z=2 \longrightarrow{2-(0)+x+y+z=2}

Therefore x + y + z = 0 \boxed{x+y+z=0}

We are asked to find ( a + 4 ) ( b + 4 ) ( c + 4 ) (a+4)(b+4)(c+4) , which is ( x + 2 ) ( y + 2 ) ( z + 2 ) (x+2)(y+2)(z+2)

Expanding gives: x y z + 2 ( x z + x y + y z ) + 4 ( x + y + z ) + 8 = 2 + 2 ( 0 ) + 4 ( 0 ) + 8 = 10 xyz+2(xz+xy+yz)+4(x+y+z)+8=2+2(0)+4(0)+8=\boxed{10}

William Isoroku - 6 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...